Majorization for certain classes of analytic functions of complex order associated with the Dziok-Srivastava and the Srivastava-Wright Convolution Operators - Murugusundaramoorthy, G.; Thilagavathi, K.; Magesh, N.
The main object of this present paper is to investigate the problem of majorization for certain classes of analytic functions of complex order associated associated with the Dziok-Srivastava and the Srivastava-Wright convolution operators. Moreover we point out some new or known consequences of our main result.
Keywords: Analytic functions; Starlike and convex functions of complex order.Q.; Qusai-subordination.; Hadamard product (convolution).; Dziok-Srivastava operator; Srivastava-Wright convolution operator